2005
DOI: 10.1111/j.1399-0004.2005.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Swedish founder MSH6 mutations, one nonsense and one missense, conferring high cumulative risk of Lynch syndrome

Abstract: Lynch syndrome, or hereditary non-polyposis colorectal cancer (HNPCC), is a cancer susceptibility syndrome caused by germline mutations in mismatch-repair genes, predominantly MLH1, MSH2 and MSH6. A majority of the mutations reported are truncating, but for MSH6, missense mutations constitute over one third. Few have been proven pathogenic in functional studies or shown to segregate in families. In this study, we show segregation of the putative pathogenic MSH6 missense mutation c.1346T>C p.Leu449Pro with micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…The study also reported a small difference in the mean age of onset between the MSH2 mutation carriers (45 years; range, 37-58 years) and the MLH1 mutation carriers (51 years; range, 35-75 years) (16). By contrast, the onset of ovarian cancer is also more frequent (33%) in families with an MSH6 mutation, although the lifetime risk of this mutation has not been established (17). The majority of ovarian cancers in Lynch syndrome are well-or moderately-differentiated and at the International Federation of Gynecology and Obstetrics stage I or II at diagnosis.…”
Section: Characteristics Of Ovarian Cancer In Lynch Syndromementioning
confidence: 81%
“…The study also reported a small difference in the mean age of onset between the MSH2 mutation carriers (45 years; range, 37-58 years) and the MLH1 mutation carriers (51 years; range, 35-75 years) (16). By contrast, the onset of ovarian cancer is also more frequent (33%) in families with an MSH6 mutation, although the lifetime risk of this mutation has not been established (17). The majority of ovarian cancers in Lynch syndrome are well-or moderately-differentiated and at the International Federation of Gynecology and Obstetrics stage I or II at diagnosis.…”
Section: Characteristics Of Ovarian Cancer In Lynch Syndromementioning
confidence: 81%
“…32,34 Unlike colorectal cancer, endometrial cancer risk is not apparently lower in MSH6 mutation carriers. 36,38 Studies have consistently reported modestly increased risks for cancers in additional sites including the stomach, ovary, urinary tract, hepatobiliary tract, brain, small intestine, and skin (sebaceous adenomas or carcinomas and keratoacanthomas) with a trend toward increased risks for pancreatic cancer. [32][33][34][35] Of these sites, gastric cancer shows marked variation in risk between different populations.…”
Section: Risk Of Cancer In Lynch Syndromementioning
confidence: 99%
“…Most of them encode truncated proteins and are readily categorized as pathogenic mutations. However, founder MMR variants with uncertain pathogenicity have also been identified (11,13,14). To investigate the functional effect of MMR variants, numerous assays at the RNA and protein level have been developed (15,16).…”
Section: Introductionmentioning
confidence: 99%